2017
DOI: 10.1126/sciadv.1700954
|View full text |Cite
|
Sign up to set email alerts
|

Climate change and water management in the biblical city of Dan

Abstract: Past climate shifts in water-stressed areas show that stagnant water could be a health threat in the context of global change.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(12 citation statements)
references
References 93 publications
0
11
0
1
Order By: Relevance
“…4; Bar-Matthews et al, 1997Bar-Matthews and Ayalon, 2011). While it has been noted that oxygen isotope ratios in speleothems cannot be used as a simple rainfall indicator (Frumkin et al, 1999;Kolodny et al, 2005;Litt et al, 2012), a similar value was suggested for the eastern Mediterranean with a decrease in annual precipitation of ∼ 30 % ( Fig. 2; Kaniewski et al, 2013).…”
Section: Lebanonmentioning
confidence: 54%
See 3 more Smart Citations
“…4; Bar-Matthews et al, 1997Bar-Matthews and Ayalon, 2011). While it has been noted that oxygen isotope ratios in speleothems cannot be used as a simple rainfall indicator (Frumkin et al, 1999;Kolodny et al, 2005;Litt et al, 2012), a similar value was suggested for the eastern Mediterranean with a decrease in annual precipitation of ∼ 30 % ( Fig. 2; Kaniewski et al, 2013).…”
Section: Lebanonmentioning
confidence: 54%
“…4; e.g., Bookman (Ken-Tor) et al, 2004;Migowski et al, 2006;Kagan et al, 2015). A similar short wet phase is recorded at Tel Akko at ∼ 4100 BP (Kaniewski et al, 2013) and ∼ 4000 BP at Tel Dan (Kaniewski et al, 2017), suggesting that minor chronological discrepancies can result from radiocarbon dating. The pollen-based environmental reconstruction from Ze'elim Gully (Dead Sea) echoes the Dead Sea level scores and suggests that drier climate conditions prevailed at ∼ 4300 BP and ∼ 3950 BP, engendering an expansion of olive horticulture during the period ∼ 4150-3950 BP, which implies milder conditions (Neuman et al, 2007a;Langgut et al, 2014Langgut et al, , 2016.…”
Section: Lebanonmentioning
confidence: 57%
See 2 more Smart Citations
“…Interestingly, during the same RCC, the Ukraine experienced a major settlement expansion, which has been attributed to societal resilience of the (cold-adapted) Cucuteni-Tripolye cultural complex (Weninger and Harper, 2015). Finally, the end of the Bronze Age around the Aegean coincided closely with the regional RCC expression of 3.1-2.9 ka BP (e.g., Rohling et al, 2009;Kaniewski et al, 2010Kaniewski et al, , 2017Cline, 2014). It appears, therefore, that there is a strong temporal relationship between RCCs in the wider eastern Mediterranean region and major archaeological changes, although-even within the Fertile Crescent (e.g., between the N-and S-Levant)-establishing such coincidences is complicated by complex interregional differences in terms of, for example, cultural trajectories, natural biodiversity, landscapes.…”
Section: Archaeological Importancementioning
confidence: 65%